GIS application in coastal management: the perspectives of government agencies in Selangor - Paiman, Tuminah; Asmawi, M. Zainora (Malaysian Institute of Planners, 2017)
The coastal area is highly considered as one of the most complex areas to be handled by the traditional planning system. In managing coastal areas, there must be integrated coastal management between various related agencies, technically and physically. The management of the coastal area depends on the coastal manager's ability to recognize and comprehend the complexity of natural coastal processes. Thus, this paper addresses how GIS tool is embedded in the coastal management system from the perspectives of government agencies in Selangor. The objectives of this research are: to identify the present integration between coastal management and GIS at government agencies in Selangor coastal districts; and to study the application of GIS and related spatial information technologies to local government officials. Data were gathered through survey. The findings show positive relationship between coastal management and GIS in Selangor. Government agencies indeed has actively been using GIS as part of the management tool of the coastal area in Selangor This may eventually lead to GIS application being recognised as a significant tool to be used in coastal management.